СПЕКТРАЛЬНИЙ АНАЛІЗ СТРУМУ В ОДНОФАЗНОМУ НАПІВМОСТОВОМУ ІНВЕРТОРІ В ПРОСТОРІ ДВОХ ЗМІННИХ - Коротеєв , І.Є. (Інститут електродинаміки НАН України, Київ, 2015)
The object of this paper is a spectrum analysis of a load current in a single-phase half-bridge inverter with PWM. The analysis is based on an extension of differential equations with one variable of time to partial differential equations with two time variables. The partial differential equation is solved with the use of the two dimensional Laplace transform. The obtained solution is described in the form of a double Fourier series. This result is transformed into such form that permits description as a spectrum in the domain of two discrete variables. References 6, figures 5.